2020
DOI: 10.1038/s41598-020-73439-9
|View full text |Cite|
|
Sign up to set email alerts
|

Tankyrase inhibitor XAV-939 enhances osteoblastogenesis and mineralization of human skeletal (mesenchymal) stem cells

Abstract: Tankyrase is part of poly (ADP-ribose) polymerase superfamily required for numerous cellular and molecular processes. Tankyrase inhibition negatively regulates Wnt pathway. Thus, Tankyrase inhibitors have been extensively investigated for the treatment of clinical conditions associated with activated Wnt signaling such as cancer and fibrotic diseases. Moreover, Tankyrase inhibition has been recently reported to upregulate osteogenesis through the accumulation of SH3 domain-binding protein 2, an adaptor protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 71 publications
(123 reference statements)
0
20
0
Order By: Relevance
“…Taking advantage of our in vitro drug screening platform of self-renewable hNPCs, we also asked whether CHIR or XAV might be cytotoxic, by measuring cell proliferation and survival. Both drugs were used in this study at the same concentration or lower as in similar studies employing human or murine ESCs, hiPSCs and other types of stem cells ( De Kumar et al, 2017 ; Malleske et al, 2018 ; Shafa et al, 2018 ; Gomez et al, 2019 ; Hamad et al, 2019 ; Qiu et al, 2019 ; Shin et al, 2019 ; Almasoud et al, 2020 ; Bataille et al, 2020 ; Bejoy et al, 2020 ; Govarthanan et al, 2020 ; Han et al, 2020 ; Kanagaki et al, 2020 ; Leigh et al, 2020 ; Yang J. et al, 2020 ; Yang Y. et al, 2020 ; Ren et al, 2021 ; Wang et al, 2021 ). When stem cells differentiate into more mature cell types, their proliferation potential is gradually reduced, until cells reach a post-mitotic fate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking advantage of our in vitro drug screening platform of self-renewable hNPCs, we also asked whether CHIR or XAV might be cytotoxic, by measuring cell proliferation and survival. Both drugs were used in this study at the same concentration or lower as in similar studies employing human or murine ESCs, hiPSCs and other types of stem cells ( De Kumar et al, 2017 ; Malleske et al, 2018 ; Shafa et al, 2018 ; Gomez et al, 2019 ; Hamad et al, 2019 ; Qiu et al, 2019 ; Shin et al, 2019 ; Almasoud et al, 2020 ; Bataille et al, 2020 ; Bejoy et al, 2020 ; Govarthanan et al, 2020 ; Han et al, 2020 ; Kanagaki et al, 2020 ; Leigh et al, 2020 ; Yang J. et al, 2020 ; Yang Y. et al, 2020 ; Ren et al, 2021 ; Wang et al, 2021 ). When stem cells differentiate into more mature cell types, their proliferation potential is gradually reduced, until cells reach a post-mitotic fate.…”
Section: Discussionmentioning
confidence: 99%
“…CHIR has been used to promote neural and neuronal differentiation in embryonic stem cells and induced pluripotent stem cells ( De Kumar et al, 2017 ; Shafa et al, 2018 ; Gomez et al, 2019 ; Qiu et al, 2019 ; Shin et al, 2019 ; Bejoy et al, 2020 ) and in several different types of neural precursors ( Yang Y. et al, 2020 ; Ren et al, 2021 ; Wang et al, 2021 ), as well as to induce trans- differentiation into neural lineages from non-neural cell types, such as skin ( Bataille et al, 2020 ; Yang J. et al, 2020 ) and mesenchymal cells ( Govarthanan et al, 2020 ). XAV has been used to promote differentiation of pluripotent stem cells into lung cells ( Malleske et al, 2018 ; Kanagaki et al, 2020 ), to increase osteogenic differentiation of mesenchymal stem cells ( Almasoud et al, 2020 ; Han et al, 2020 ), and to promote generation of cardiomyocytes ( Hamad et al, 2019 ; Leigh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding osteoblastogenesis, a critical role of PARP1 was also previously reported. Our previous study demonstrated that PARP inhibitor PJ34 attenuated mesenchymal osteoblast differentiation via the BMP-2 signaling pathway in vitro [ 53 ], which suggested a progressive effect on osteoclastogenesis; furthermore, another study showed that tankyrase inhibitor XAV-939 enhances osteoblastogenesis and mineralization of human skeletal mesenchymal stem cells via TNF, NF-κB, and STAT signaling [ 54 ]. Thus, the effect of olaparib is suggested to be pivotal on other pathways, or this role could be due to the differences in the derived cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Small molecule inhibitors targeting specific intracellular signalling pathways are currently used in vitro as a biochemical tool to identify the molecular mechanisms involved in stem cell differentiation into osteoblast lineages [ 15 , 20 , 22 , 24 , 25 , 26 , 27 ]. Here, we identified a small molecule Fedratinib, a potent JAK2 inhibitor [ 28 ], through a small molecule library screen [ 15 ], as a powerful inhibitor of osteoblastic differentiation of hMSC-TERT cells.…”
Section: Introductionmentioning
confidence: 99%